Evolution and genetic diversity of the Spain23F-ST81 clone causing adult invasive pneumococcal disease in Barcelona (1990-2012). - Domenech, A; Ardanuy, C; Grau, I; Calatayud, L; Pallares, R; Fenoll, A; Brueggemann, A; Liñares, J (Oxford University Press, 2014)
OBJECTIVES: We aimed to analyse the clinical epidemiology and genetic diversity of invasive pneumococcal disease (IPD) episodes attributed to the Spain(23F)-ST81 (PMEN1) clone. METHODS: Fifty-eight (2.7%) of 2117 invasive pneumococci isolated from adult patients during the 1990-2012 period shared a PFGE pattern related to the PMEN1 clone. The genotype was confirmed by multilocus sequence typing. The pbp2x, pbp1a, pbp2b and pspA genes were PCR-amplified and sequenced. Polymorphisms in the pspC gene were identified by PCR restriction fragment length polymorphism. The presence of transposons with erythromycin and tetracycline resistance determinants was detected by PCR. RESULTS: The prevalence of the PMEN1 clone increased from 0.8% in 1991 to 6.2% in 2001, and decreased to 0% in 2010-12, concomitant with the introduction of the seven-valent pneumococcal conjugate vaccine for children. A total of 93.1% of patients had pneumonia, meningitis or peritonitis; 87.9% of patients had associated underlying diseases, mainly cancer, chronic obstructive pulmonary disease and diabetes. Two closely related sequence types (STs) (ST81, n = 52; ST85, n = 6) were detected, with different serotypes: 23F (n = 42), 19A (n = 9) and 19F (n = 6). All the isolates were resistant to penicillin, co-trimoxazole and chloramphenicol. All the isolates also shared the same pbp1a allele, whereas multiple alleles of pbp2b, pbp2x, pspA and pspC were detected. Of the isolates, 89.7% were tetracycline resistant and 60.3% (n = 35) were macrolide resistant, and resistance was associated with different Tn916-like transposons. CONCLUSIONS: Adult IPD caused by this clone was mainly detected in patients with underlying conditions, and genetic variability was observed among PMEN1 isolates collected in our area over the past 20 years.